Identifying Risks on Human Activities in Power Plants During The COVID-19 Pandemic - Rahmah, Adinda Syafira; Ambarwati, Rita; Sumartik, Sumartik; Dedy, Dedy (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2023)
The situation caused by the pandemic has prompted every company to protect the safety of its employees. The energy/electricity industry cluster continues to operate despite the need for social restrictions in several locations, including the East Java power plant. This study identifies the risks of human activities at power plants throughout the COVID-19 pandemic. This study used quantitative data information gleaned from interviews, observations, and questionnaires. This research a technique that combines Failure Mode Effect Analysis (FMEA). Of the 17 activities carried out in the risk analysis using the FMEA method, the activities that show the five locations with the highest RPN scores are the workshop, warehouse, administration building, Coal Handling Control Building [CHCB], and employee training. We will integrate this analysis with the risk analysis that has been prepared previously by the applicable administrative regulations. Human resource risk management is concerned with enhancing productivity among workers by lowering days ignored because of a lack of jobs. The results can serve as recommendations for evaluating COVID-19 risk management and preventive measures in power generation companies.